Ecological performance of construction materials subject to ocean climate change - Davis, Kay L.; Coleman, Melinda A.; Connell, Sean D.; Russell, Bayden D.; Gillanders, Bronwyn M.; Kelaher, Brendan P. (Marine environmental research, 2017)
Artificial structures will be increasingly utilized to protect coastal infrastructure from sea-level rise and storms associated with climate change. Although it is well documented that the materials comprising artificial structures influence the composition of organisms that use them as habitat, little is known about how these materials may chemically react with changing seawater conditions, and what effects this will have on associated biota. We investigated the effects of ocean warming, acidification, and type of coastal infrastructure material on algal turfs. Seawater acidification resulted in greater covers of turf, though this effect was counteracted by elevated temperatures. Concrete supported a greater cover of turf than granite or high-density polyethylene (HDPE) under all temperature and pH treatments, with the greatest covers occurring under simulated ocean acidification. Furthermore, photosynthetic efficiency under acidification was greater on concrete substratum compared to all other materials and treatment combinations. These results demonstrate the capacity to maximise ecological benefits whilst still meeting local management objectives when engineering coastal defense structures by selecting materials that are appropriate in an ocean change context. Therefore, mitigation efforts to offset impacts from sea-level rise and storms can also be engineered to alter, or even reduce, the effects of climatic change on biological assemblages. [Display omitted] •Concrete supported a greater cover of turf than granite or HDPE under all temperature and pH treatments.•Regardless of material type, algal turf cover was greatest when exposed to conditions simulating ocean acidification.•Photosynthetic efficiency was greatest on concrete under acidification than all other materials and treatment combinations.•Concrete may facilitate turfs over other artificial materials under future ocean conditions.•Mitigation efforts to offset impacts of climate change can also be engineered to alter the effects on biological assemblages.